1996
DOI: 10.1021/jm950786p
|View full text |Cite
|
Sign up to set email alerts
|

2,4-Diamino-5-deaza-6-Substituted Pyrido[2,3-d]pyrimidine Antifolates as Potent and Selective Nonclassical Inhibitors of Dihydrofolate Reductases

Abstract: Fifteen novel nonclassical and two classical 2,4-diamino-6-(benzylamino)pyrido[2,3-d]pyrimidine antifolates were synthesized as potential inhibitors of Pneumocystis carinii, (pc) Toxoplasma gondii, (tg) rat liver (rl), and human (h) recombinant dihydrofolate reductases (DHFR). These analogues lack a 5-methyl substitution which has been shown to be important for increased hDHFR inhibitory activity. In addition, they contain a reversal of the C9-N10 bridge present in folates and most antifolates. The synthesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
72
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(73 citation statements)
references
References 33 publications
0
72
1
Order By: Relevance
“…Trimetrexate, which is approved as a second line agent against P. carinii infections must be used along with the folate cofactor, leucovorin, to rescue host cells [23]. Gangjee et al [24] have reported a generalization in the structure-activity/selectivity of the pyrido [2,3-d]pyrimidine ring system which indicates that selected analogues of the 5,10-dimethyl substituted series of general structure 1 as well as selected analogues containing a 9-methyl substitution of general structure 2 [14] provide significant potency and selectivity for P. carinii and/or T. gondii dihydrofolate reductase.…”
Section: Jan-feb 2001 213mentioning
confidence: 99%
See 1 more Smart Citation
“…Trimetrexate, which is approved as a second line agent against P. carinii infections must be used along with the folate cofactor, leucovorin, to rescue host cells [23]. Gangjee et al [24] have reported a generalization in the structure-activity/selectivity of the pyrido [2,3-d]pyrimidine ring system which indicates that selected analogues of the 5,10-dimethyl substituted series of general structure 1 as well as selected analogues containing a 9-methyl substitution of general structure 2 [14] provide significant potency and selectivity for P. carinii and/or T. gondii dihydrofolate reductase.…”
Section: Jan-feb 2001 213mentioning
confidence: 99%
“…Bicyclic 2,4-diamino nonclassical dihydrofolate reductase inhibitors related to the pteridines [13], pyrido [2,3-d]pyrimidines [14], pyrido [3,2-d]pyrimidines [15], quinazolines [16], pyrrolo [2,3-d]pyrimidines [17], furo [2,3-d]pyrimidines [18], and thieno [2,3-d]pyrimidines [19] among others [20,21] have been synthesized as potential potent and selective inhibitors of dihydrofolate reductase from P. carinii and T. gondii. Though structureactivity/selectivity correlations for each bicyclic system have been developed no structure-activity relationship across the different heterocyclic systems is possible at this time and each heterocyclic system needs to be considered separately.…”
mentioning
confidence: 99%
“…They show dihydrofolate reductase inhibition and antitumor [3][4][5] as well as diuretic properties [6]. Moreover, some of these compounds possess antimicrobial [7,8], antibacterial [9,10], and cytotoxic activities [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the other objective of the present study is to prepare pyrido [2,3-d]pyrimidines. The interest in the synthesis of the later compounds is due to the fact that various derivatives of pyrido [2,3-d]pyrimidine were reported to be useful as antitumor [15], antimicrobial [16], antibacterial [17], antifolate [18], anticonvulsants [19], antileishmanial [20], antiinflammatory [21], diuretic, antiaggressive activity [22] and antiviral activity [23]. …”
Section: Introductionmentioning
confidence: 99%